Meta-Analysis: The Effect of Vaccination on the COVID-19 Infection - Farida Nurhayati; Setyo Sri Rahardjo; Bhisma Murti (Journal of Epidemiology and Public Health, 2023)
Background: The Indonesian government has determined that COVID-19 is a public health emergency and a non-natural national disaster that requires multi-strategy management. Strategies such as implementing health protocols and vaccination efforts to break the chain of transmission of COVID-19 must continue to be carried out massively. This study aims to analyze the effect of vaccination on COVID-19 infection.Subjects and Method: This study is a systematic review and meta-analysis, with PICO as follows Population= population aged ≥18 years. Intervention= Vaccination. Comparison= Not vaccinated. Outcome= COVID-19 infection. The articles used in this study were obtained from several databases including PubMed, Google Scholar, and Scopus. These articles were collected over 2 months. The keywords to search for articles are as follows “Vaccine OR Vaccination AND (Infection OR Trans-mission) AND COVID-19 OR SARS-CoV-2”. The articles included in this study were full-text articles with a retrospective or prospective cohort study design. Articles are collected using PRISMA flow diagrams. Articles were analyzed using the Review Manager 5.3 application.Results: A total of 10 articles reviewed in this meta-analysis study originating from England, Spain, France showed that COVID-19 vaccination is effective in reducing the risk of COVID-19 infection. People who were given the COVID-19 vaccine had a 0.22 times risk of being infected compared to those who were not vaccinated, and the reduced risk was statistically significant (aHR= 0.22; 95% CI= 0.13 to 0.36; p <0.001).Conclusion: COVID-19 vaccination is effective in reducing the risk of COVID-19 infection. Keywords: vaccination, infection, COVID-19, SARS-COV-2 Correspondence:Farida Nurhayati. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: faridafay19@gmail.com. Mobile: +6285642154353.